FUNGSI DAN PERANAN KONSELING DALAM MENINGKATKAN KESE-JAHTERAAN SANTRI DI PESANTREN - Sadza Magfirotul Huda; Sri Oktavia Aida Fitri; Lina Amalina; Agus Sukirno (STKIP Subang, 2026)
This study aims to examine the roles and functions of counseling in improving the well-being of students (santri) in Islamic boarding schools (pesantren). The method used in this study is a literature review by analyzing various journal articles related to the research topic. The results show that counseling services have preventive, curative, and developmental functions in helping students deal with various problems such as stress, anxiety, and difficulties in adapting to the boarding school environment. Furthermore, counseling also contributes to enhancing emotional maturity, independence, as well as the development of students’ character and moral values. Counseling services in pesantren are provided in various forms, such as individual counseling, group counseling, and consultation services, which complement each other in the student development process. The implementation of counseling services integrated with Islamic values has been proven to improve students’ mental health and psychological well-being in a sustainable manner. Therefore, counseling becomes an essential component in supporting the overall development of students.